2020
DOI: 10.1371/journal.pntd.0008268
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of bloodstream infections among febrile adolescents and adults attending Yangon General Hospital, Yangon, Myanmar

Abstract: Data on causes of community-onset bloodstream infection in Myanmar are scarce. We aimed to identify etiological agents of bloodstream infections and patterns of antimicrobial resistance among febrile adolescents and adults attending Yangon General Hospital (YGH), Yangon, Myanmar. We recruited patients �12 years old with fever �38˚C who attended YGH from 5 October 2015 through 4 October 2016. A standardized clinical history and physical examination was performed. Provisional diagnoses and vital status at discha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 62 publications
1
16
2
Order By: Relevance
“…The prevalence of SA infection among biological specimens sent for culture and drug susceptibility testing in this study were five times higher than the results reported in the previous two studies from Myanmar, both of which were conducted in a single hospital and only focused on blood specimens [ 17 , 18 ]. Our study also showed a higher SA prevalence than the studies undertaken in India and Nepal [ 19 , 20 ].…”
Section: Discussioncontrasting
confidence: 75%
“…The prevalence of SA infection among biological specimens sent for culture and drug susceptibility testing in this study were five times higher than the results reported in the previous two studies from Myanmar, both of which were conducted in a single hospital and only focused on blood specimens [ 17 , 18 ]. Our study also showed a higher SA prevalence than the studies undertaken in India and Nepal [ 19 , 20 ].…”
Section: Discussioncontrasting
confidence: 75%
“…Haematological and biochemical investigations provide additional valuable information about comorbidities and organ dysfunction, which may have a significant impact on management (Rhodes et al, 2017;Shetty et al, 2018;Singer et al, 2016). Microbiological investigations play an essential role in identifying the causative pathogen and, in an era of evolving antimicrobial resistance, recommending appropriate therapy (Dondorp et al, 2018;Myat et al, 2020;Ye Lynn et al, 2019). Meanwhile radiology assists in identifying the site of infection, facilitating the selection of empirical regimens and expediting source control (Abe et al, 2019;Williams et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Myanmar is one of the poorest countries in South East Asia and sepsis is the most common cause of in-hospital death (Ye Lynn et al, 2019). Although the country has made significant progress against infections like malaria (Mu et al, 2016), it remains one of the world's 30 high tuberculosis (TB) burden countries (World Health Organization, 2019;Thit, 2017), HIV affects 0.8% of adults aged 15-49 years (UNAIDS, 2018), and antimicrobial resistance is a significant and growing issue (Myat et al, 2020;Ye Lynn et al, 2019). This study was performed to determine the ability of several commonly used disease severity scores to predict the clinical course of patients with evidence of community-acquired sepsis in resource-limited tropical settings like Myanmar.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective analysis of blood culture data from Yangon General Hospital, a tertiary hospital for adults, between 2005 to 2013 reported 37/45 E. coli isolates as resistant to ceftriaxone; however confirmatory testing for ESBLs was not performed. 8 Another study of bloodstream infections in patients in three hospitals in Yangon conducted between July and December 2014 confirmed 16/42 (38%) Gram-negative isolates were ESBL-producing Enterobacterales and 6/42 (14%) were New Delhi metallo-beta lactamase (NDM) carbapenemase producers. 9 In another tertiary hospital in the north of Yangon in 2016, almost half (49.1%) of all E. coli isolates were ESBL producers.…”
Section: Introductionmentioning
confidence: 99%